EFFECTIVENESS OF THE SEATTLE HEART FAILURE MODEL IN PREDICTING THE LONG-TERM PROGNOSIS AMONG MEN WITH CORONARY HEART DISEASE - O. A. Krasnova; M. Yu. Sitnikova; S. G. Ivanov; P. A. Fedotov (Российский кардиологический журнал, 2012)
Aim. To assess the life prognosis in patients with chronic heart failure (CHF) – male residents of St. Petersburg – according to the Seattle Heart Failure Model (SHFM) and compare it to the observed survival. Material and methods. A retrospective survival analysis was performed in 135 patients with Functional Class (FC) II–IV CHF of ischemic aetiology. At baseline, anamnestic, clinical, functional, and instrumental data were collected. Observed five-year all-cause mortality was compared to that predicted by SHFM. Statistical analyses were performed in SPSS 15.0. Results. Over the five years of the follow-up (60 months), 67% of the participants (n=88) survived. Observed one-, two-, and five-year survival in FC II CHF patients was 95%, 92%, and 74%, respectively. In FC III CHF patients, the respective figures were 92%, 85%, and 61%. Predicted one-, two-, and five-year survival, according to the mean risk estimates by SHFM, was 98%, 95%, and 89% for FC II CHF individuals, and 96%, 92%, and 80%, respectively, for the FC III CHF participants. Therefore, for the first five years of the follow-up, the SHFM predictions exceeded the observed survival by 3–15% and 4–19% in CHF patients with FC II and FC III, respectively (p1,2<0,05). There was a statistically significant association between the observed survival and smoking, concomitant chronic obstructive pulmonary disease, and hypertension duration before the CHF manifestation. Conclusion. The SHFM markedly overestimated the observed survival in male patients with systolic CHF – St. Petersburg residents. Therefore, in this population, this instrument cannot be recommended for the CHF prognosis assessment. There is a need to develop a survival model for Russian patients with CHF, which would incorporate additional determinants of adverse prognosis.>< 0,05). There was a statistically significant association between the observed survival and smoking, concomitant chronic obstructive pulmonary disease, and hypertension duration before the CHF manifestation. Conclusion. The SHFM markedly overestimated the observed survival in male patients with systolic CHF – St. Petersburg residents. Therefore, in this population, this instrument cannot be recommended for the CHF prognosis assessment. There is a need to develop a survival model for Russian patients with CHF, which would incorporate additional determinants of adverse prognosis.